Isolation and characterisation of polymorphic microsatellite markers in the progeny of nine mating groups of snakeheads - Zhou, Aiguo; Lv, Zijun; Xie, Shaolin; Chen, Jintao; Chen, Yanfeng; Zou, Jixing (Indian Journal of Fisheries, 2015)
Nine mating groups of snakeheads (Channa maculata and Channa argus) have been successfully bred in our laboratory. During the course of this research, five polymorphic microsatellite loci were initially screened out from the nine populations, which were isolated and characterised. A total of 360 individuals from the nine populations have been genotyped and forty three alleles were found. The number of observed and effective alleles ranged from 6 to 12 and from 3.8907 to 7.4083 per locus. Average numbers of alleles and effective alleles were 8.60 and 5.03, respectively. Average number of observed alleles in each population varied from 2.2 to 4.4, while the mean number of effective alleles varied from 1.78 to 3.10. Average observed heterozygosity (HO) and expected heterozygosity (HE) in the nine populations ranged from 0.1600 to 0.4700 and from 0.4082 to 0.6490, respectively. Polymorphism information content (PIC) varied from 0.3351 to 0.5778. Among the forty five population loci, thirty eight showed significant deviation from the Hardy-Weinberg equilibrium. These results demonstrated great significance for the evaluation and conservation of new species and also provided the basic material for predicting heterosis as well as for breeding of new varieties with economic value.